Contradictions of Collective Security Model: Modern Historiography on the Evolution of the Versailles System of International Relations in the 1930s - A. A. Vershinin (Vestnik MGIMO-Universiteta)
The article attempts to find out the reasons for the failure of the collective security system in Europe, developed to counter German revisionism in the second half of the 1920s – early 1930s. Research literature tends to consider collective security not just as a diplomatic tool, but as a quality of international system developed after the First World War based on the idea of indivisible security with universal international organization presiding over it to deal with problems of war and peace. The principle of the balance of power and war itself as a means of international politics thus lost their legitimacy.Historians agree that the system proved unsuitable for the challenges of the early 1930s, demonstrated by the Ethiopian War and the Rhineland Crisis. Two alternative ways eventually developed to deal with the inconsistences of the early collective security system: «appeasement» project, initiated by British diplomacy; and the Soviet idea of military-political deterrence through coalition building. Modern historiography views «appeasement» as the idea presupposing the creation of a European Directory, which would have taken on the functions of resolving international contradictions. Historians see the reasons for its failure in an incorrect assessment of Hitler's policy due to thinking in the spirit of collective security. The position of the USSR is more contested among historians. In recent works, however, there appears the consensus that the reason for the failure of the project of a military-political alliance aimed at containing Germany was the unwillingness of the West to strategic interaction with Moscow and its adherence to the principles of «new diplomacy» at a time when it already lost their relevance.